Morphological and histological characters of penile organization in eleven species of molossid bats - Comelis, Manuela T. [UNESP]; Bueno, Larissa M. [UNESP]; Góes, Rejane M. [UNESP]; Taboga, S. R. [UNESP]; Morielle-Versute, Eliana [UNESP] (Elsevier, 2018)
The penis is the reproductive organ that ensures efficient copulation and success of internal fertilization in all species of mammals, with special challenges for bats, where copulation can occur during flight. Comparative anatomical analyses of different species of bats can contribute to a better understanding of morphological diversity of this organ, concerning organization and function. In this study, we describe the external morphology and histomorphology of the penis and baculum in eleven species of molossid bats. The present study showed that penile organization in these species displayed the basic vascular mammalian pattern and had a similar pattern concerning the presence of the tissues constituting the penis, exhibiting three types of erectile tissue (the corpus cavernosum, accessory cavernous tissue, and corpus spongiosum) around the urethra. However, certain features varied among the species, demonstrating that most species are distinguishable by glans and baculum morphology and glans histological organization. Major variations in glans morphology were genus-specific, and the greatest similarities were shared by Eumops species and N. laticaudatus. The greatest interspecific similarities occurred between M. molossus and M. rufus and between Eumops species. Save for M. molossus and M. rufus, morphology of the baculum was species-specific; and in E. perotis, it did not occur in all specimens, indicating that it is probably under selection. In the histological organization, the most evident differences were number of septa and localization of the corpora cavernosa. In species with a baculum (Molossus, Eumops and Nyctinomops species), the corpora cavernosa predominantly occupied the dorsal region of the penile glans and is associated with the proximal (basal) portion of the baculum. In species that do not have a baculum (Cynomops, Molossops and Neoplatymops species), the corpora cavernosa predominantly occupied the ventro-lateral region of the glans.
Keywords: Accessory cavernous tissue; Baculum; Glans penis; Molossidae